Analysis Of The Effect Of Co-Firing On Boiler Loading Limitations Using Computational Fluid Dynamic (CFD) Methods - Prabowo Prabowo; Muhammad Ramon Mudman (Jurnal Syntax Admiration, 2025)
The increasing depletion of high-calorific coal resources has driven coal-fired power plants (PLTU) to switch to low-calorific coal with calorific values ranging from 4,200 to 4,800 kcal/kg. Simultaneously, the Indonesian government aims to achieve a renewable energy mix of 23% by 2025 and 31.2% by 2050, promoting the co-firing of biomass with coal at rates of 5% to 12%. However, this transition presents operational challenges, such as altered combustion characteristics, overheating in superheater zones, and increased slagging and fouling potential. This study aims to analyze the impact of co-firing biomass with coal on boiler performance at a 600 MW PLTU using Computational Fluid Dynamics (CFD) simulations. Data inputs include coal specifications and biomass mixing ratios of 3%, 5%, 8%, and 12%. Simulations were conducted using Ansys Fluent software to assess variations in temperature, pressure, and flow distribution. The results indicate that increasing biomass percentages reduces combustion temperatures and alters the distribution of key combustion byproducts, such as H₂O and SO₂. A higher biomass ratio mitigates the risk of overheating but requires careful operational adjustments to maintain efficiency. The findings support the optimization of co-firing operations, contributing to reduced carbon emissions and compliance with Indonesia’s renewable energy targets. This study provides actionable insights for improving PLTU performance while aligning with sustainable energy goals.